The relationship between job motivation and job satisfaction in non academic staff at UiTM City Campus Malacca / Nur Hayati Hassan - Hassan, Nur Hayati (Faculty of Office Management and Technology, 2013)
The study investigates the relationship between Job Motivation and Job Satisfaction. Job Motivation has been treated as an independent and Job Satisfaction as dependent variable. The selected respondents for the study are the employees at UiTM City Campus Malacca. All respondents for the study are from non academic staffs that work at the institution. The primary data will be collected by the researcher through a questionnaire and based on five pointer Likert scale. All data received will be analyzed by SPSS Version 18.0.